Opportunities and challenges of digitalizing tax administration in Malaysia: Toward efficient, inclusive, and secure governance - Wan Mustafa, Wan Muzlaina; Mat Jusoh, Yusri Huzaimi; Bahari, Rosliza; Ishak, Rosbi; Abd Rahman, Samsuria; Mustapha, Mazlan (International Journal of Accounting, Finance and Business, 2025)
The digitalization of tax administration has emerged as a transformative strategy for enhancing efficiency, transparency, and compliance in public sector governance. In Malaysia, initiatives such as the HASIL e-Filing system, the MyTax portal, and e-Stamping mark significant progress toward modernizing tax services in line with the Malaysia Digital Economy Blueprint (MyDIGITAL). This study explores the opportunities and challenges associated with Malaysia’s transition to digital tax systems. Drawing on global and local evidence, the findings highlight key benefits, including cost reduction, improved taxpayer compliance, enhanced user experience, and the integration of big data analytics to support policy decision-making. Digital platforms have also fostered inclusivity by expanding access to tax services, particularly during the COVID-19 pandemic. However, significant challenges persist, such as cybersecurity risks, resistance to change among stakeholders, the digital divide between urban and rural communities, and difficulties in integrating legacy systems with new technologies. Issues of data accuracy and public trust further complicate implementation. The study argues that addressing these challenges through investments in digital infrastructure, cybersecurity frameworks, and digital literacy programs is crucial for ensuring sustainable adoption. It concludes that Malaysia’s experience provides valuable lessons for other developing countries undergoing similar digital transitions, bridging the gap between global best practices and localized realities. By offering a nuanced understanding of both opportunities and barriers, this research contributes to the discourse on digital governance and provides actionable recommendations for policymakers, tax authorities, and stakeholders seeking to optimize digital tax administration.